Don Tillman's standardized meal system : recipes & tips from the star of the Rosie novels - Simsion, Graeme C. (Text Publishing, 2019)
'So, you cook this same meal every Tuesday, right?' 'Correct.' I listed the eight major advantages of the Standardised Meal System. 1. No need to accumulate recipe books. 2. Standard shopping list-hence very efficient shopping. 3. Almost zero waste-nothing in the refrigerator or pantry unless required for one of the recipes. 4. Diet planned and nutritionally balanced in advance. 5. No time wasted wondering what to cook. 6. No mistakes, no unpleasant surprises. 7. Excellent food, superior to most restaurants at a much lower price (see point 3). 8. Minimal cognitive load required. 'Cognitive load?' 'The cooking procedures are in my cerebellum-virtually no conscious effort is required.' 'Like riding a bike.' 'Correct.' Here at last, by popular demand, is the weekly system of food preparation that Professor Don Tillman, star of the Rosie trilogy, lives by-everything from his signature lobster salad to the world's best risotto, across the four seasons. This essential guide also includes handy tips about losing weight, mixing cocktails and stress-free entertaining. Don Tillman's Standardised Meal System will not only show you how to make delicious meals- it will open your mind a different way of shopping, cooking and living. The Don Tillman way.